Pelatihan Penganggaran Material: Studi Kasus Pelalu UMKM Di Kabupaten Majene - Anwar Anwar; Romansyah Sahabuddin; Nurman Nurman; Chalid Imran Musa; Rahmat Riwayat Abadi (Institut Teknologi dan Bisnis Semarang, 2024)
This service aims to provide knowledge to MSME players to be able to increase the competitiveness and sustainability of their businesses, as well as strengthen their role in the local economy. Apart from that, MSME players can also build efficient local distribution relationships by partnering with local producers or cooperatives to supply raw materials directly, thereby reducing dependence on supplies from outside the city. To overcome these problems, targeted support is needed for MSMEs. This support includes increasing knowledge in budget management, optimizing the use of raw materials, implementing effective procurement strategies, and using modern financial management technology and tools. With concrete and sustainable solutions, it is hoped that MSMEs can increase production capacity, strengthen the local economy, and achieve greater and more sustainable success. Overall, this training succeeded in building a collaborative and sustainable learning community, where participants can continue to share knowledge and experiences for their professional development.